(untitled) (Proceeding of Dakwah Saizu International Conference, 2023)
Moderation becomes a necessity for religious communities in organizing social life when learning is shown to provide religious values that prioritize thoughts based on the socio-cultural community so that learning is not only aimed at providing knowledge for students but on the other hand is how to realize prosperity and upholding human values, especially in the realm of respecting diversity within a frame of moderation. The method in this research is qualitative with a descriptive approach. The Practical Role of Multiculturalism Education at MAN 2 Banyumas in order to strengthen the understanding of religious tolerance for students is carried out through various activities such as through the practice of worship and congregational prayer; understanding Aswaja is also taught, accompanied by guidance in reading the Al-Qur’an and reading and writing the Al-Qur’an. (BTQ). The obligation to wear Muslim clothing for female students is also teaching to support the good quality of the learning experience and ongoing education. Apart from that, there is a collaboration between the PAI curriculum and an understanding of religious tolerance, which can develop students into moderate individuals. There are several teachings to practice an understanding of religious tolerance, namely, rejecting hate speech both outside and inside the school, fostering peaceful attitudes and peace in the social environment, and building harmony and tolerance with the existence of different groups.